Politics of Water Resource Management in the Indus River Basin: A Study of the Partition of Punjab - Muhammad Nawaz Bhatti (IDEA PUBLISHERS, 2020)
The British Government of India divided the Muslim majority province of Punjab into Eastern and Western Punjab. But the partition line was drawn in a manner that headworks remained in India and irrigated land in Pakistan. The partition of Punjab was not scheduled in the original plan of the division of India. Why was it partitioned? To answer this question, the study in the first instance tries to explore circumstances, reasons, and conspiracies which led to the partition of Punjab which led to the division of the canal irrigation system and secondly, the impact of partition on water resource management in the Indus River Basin. Descriptive, historical, and analytical methods of research have been used to draw a conclusion. The study highlights the mindset of Indian National Congress to cripple down the newly emerging state of Pakistan that became a root cause of the partition of Punjab. The paper also highlights why India stopped water flowing into Pakistan on 1st April 1948 and the analysis also covers details about the agreement of 4th May 1948 and its consequences for Pakistan.